2006
DOI: 10.1152/ajpendo.00096.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rosiglitazone treatment restores AMPKα2 activity in insulin-resistant rat skeletal muscle

Abstract: (RSG) is an insulin-sensitizing thiazolidinedione (TZD) that exerts peroxisome proliferator-activated receptor-␥ (PPAR␥)-dependent and -independent effects. We tested the hypothesis that part of the insulinsensitizing effect of RSG is mediated through the action of AMPactivated protein kinase (AMPK). First, we determined the effect of acute (30 -60 min) incubation of L6 myotubes with RSG on AMPK regulation and palmitate oxidation. Compared with control (DMSO), 200 M RSG increased (P Ͻ 0.05) AMPK␣1 activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 39 publications
4
43
1
Order By: Relevance
“…Also, high fat diet feeding significantly decreases phospho-AMPK in the liver and muscles of rodents (13,14). AMPK activity is reduced in aortic endothelium or skeletal muscle of obese rats compared with lean animals (15,16). These data raise the possibility that chronic exposure of fatty acids to cells inhibit AMPK activation.…”
mentioning
confidence: 92%
“…Also, high fat diet feeding significantly decreases phospho-AMPK in the liver and muscles of rodents (13,14). AMPK activity is reduced in aortic endothelium or skeletal muscle of obese rats compared with lean animals (15,16). These data raise the possibility that chronic exposure of fatty acids to cells inhibit AMPK activation.…”
mentioning
confidence: 92%
“…In this regard, we have previously demonstrated that chronic rosiglitazone restores AMPK activation in the skeletal muscle of fa/fa Zucker rats, a model that displays reduced AMPK activation as a result of deficient leptin signaling (20). In contrast, high-fat feeding in the present study resulted in a ϳ36% increase in AMPK␣2 activity (Fig.…”
Section: Fig 3 Skeletal Muscle Ampk Activity and Protein Expressionsupporting
confidence: 47%
“…AMPK activity and AMPK subunit protein expression. AMPK activity, pT172 phosphorylation, and total protein content were analyzed as previously described (20). Activities were calculated as picomoles of phosphate incorporated into the SAMS peptide per minute, per milligram of protein subjected to immunoprecipitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…89,90 Since AMPK is important for mitochondrial biogenesis through it's effects on the transcriptional coactivator PGC-1α, 91,92 it seems reasonable that mitochondrial dysfunction may be due to reduced AMPK activity and that the prolonged inhibition of TNF signaling as observed in ob/ob TNFR -/-may be effective in reversing these defects due to increased mitochondrial biogenesis. Supporting this idea are findings that the chronic treatment of ob/ob mice with the commonly used anti-diabetic drug rosiglitazone, which is an AMPK activator 93,94 and suppressor of TNFα production, 95,96 reverses defects in mitochondrial density in adipose tissue. 97 Similarly, a recent study has shown that chronic activation of AMPK by the hormone adiponectin, which alike to rosiglitazone also reduces TNFα production, increases muscle mitochondrial biogenesis.…”
Section: Tnfα Neutralization or Genetic Ablation Of Tnf Receptors Resmentioning
confidence: 93%